2021
DOI: 10.3390/ma14020376
|View full text |Cite
|
Sign up to set email alerts
|

Surface Reformation of Medical Devices with DLC Coating

Abstract: We evaluated the adhesion, friction characteristics, durability against bodily acids, sterilization, cleaning, and anti-reflection performance of diamond-like carbon (DLC) coatings formed as a surface treatment of intracorporeal medical devices. The major coefficients of friction during intubation in a living body in all environments were lower with DLC coatings than with black chrome plating. DLC demonstrated an adhesion of approximately 24 N, which is eight times stronger than that of black chrome plating. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…A corrosive liquid or gas can penetrate the base metal. Some studies have shown that the use of DLC coatings instead of chromium plating could improve the mechanical, tribological and corrosive properties of the material [28,29]. However, in addition to this substitution, another possibility is to use the DLC coating directly on a chromium layer, maintaining the esthetics and bright properties of the chromium layer.…”
Section: Introductionmentioning
confidence: 99%
“…A corrosive liquid or gas can penetrate the base metal. Some studies have shown that the use of DLC coatings instead of chromium plating could improve the mechanical, tribological and corrosive properties of the material [28,29]. However, in addition to this substitution, another possibility is to use the DLC coating directly on a chromium layer, maintaining the esthetics and bright properties of the chromium layer.…”
Section: Introductionmentioning
confidence: 99%
“…DLC coatings are applied to the surface of injection molds, and the electrical properties and biocompatibility cause a growing interest in using these coatings in medicine. This also improves operational features of coatings operating in corrosive [2,3] and biocorrosive aggressive environments [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Still, they present several shortcomings such as the practical operative life of the implanted devices. Terefore, fnding a way for such prosthetic systems to last for a long time is one of the key factors why DLC coatings attract great interest in biomedical applications [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%